The Influence of the Mobile Legends E-Sport Phenomenon on Student Financial Behavior - Galuh Ayu Wijaya; Fitri Santi (SAFE-Network, 2024)
This research aims to examine the influence of the Mobile Legends e-sport phenomenon on student financial behavior. Using a quantitative approach, this research collected data from a number of respondents who were active students and also Mobile Legends players. Data analysis was carried out using statistical methods to find out whether there was a significant relationship between the hobby of playing Mobile Legends and students' financial management. The research results show that there is a significant influence of the Mobile Legends e-sports phenomenon on student financial behavior. Students who actively play Mobile Legends tend to have poor financial behavior compared to students who don't play e-sports. This research provides new insights into the impact of online games on broader aspects of life, especially in the context of personal financial management.